One Essay On Dissertation Formats In Economics - Stock, Wendy A; Siegfried, John J (American Economic Review, 2013)
Dissertations in economics have changed dramatically over the past forty years, from primarily treatise-length books to sets of essays on related topics. We document trends in essay-style dissertations across several metrics, using data on dissertation format, PhD program characteristics, demographics, job market outcomes, and early career research productivity for two large samples of US PhDs graduating in 1996-1997 or 2001-2002. Students at higher ranked PhD programs, citizens outside the United States, and microeconomics students have been at the forefront of this trend. Economics PhD graduates who take jobs as academics are more likely to have written essay-style dissertations, while those who take government jobs are more likely to have written a treatise. Finally, most of the evidence suggests that essay-style dissertations enhance economists' early career research productivity.